The Japanese negotiator : - March, Robert M. (Kodansha International, 1988)
Every negotiator faces the same vexing question; How can i figure out what the person on the other side reaaly thinks and wants, and what is the real meaning of his words and action? If you and your opponent share a common language and culture, you can often fall back on insight and intuition